Magnetic Fields in Low-Mass Stars: An Overview of Observational Biases. Issue Volume 9:Issue S302(2013) (7th August 2014) - Reiners, Ansgar
Abstract: Stellar magnetic dynamos are driven by rotation, rapidly rotating stars produce stronger magnetic fields than slowly rotating stars do. The Zeeman effect is the most important indicator of magnetic fields, but Zeeman broadening must be disentangled from other broadening mechanisms, mainly rotation. The relations between rotation and magnetic field generation, between Doppler and Zeeman line broadening, and between rotation, stellar radius, and angular momentum evolution introduce several observational biases that affect our picture of stellar magnetism. In this overview, a few of these relations are explicitly shown, and the currently known distribution of field measurements is presented.